2004
DOI: 10.1079/bjn20041173
|View full text |Cite
|
Sign up to set email alerts
|

Inter-relationship of microbial activity, digestion and gut health in the rabbit: effect of substituting fibre by starch in diets having a high proportion of rapidly fermentable polysaccharides

Abstract: Caecal microbial activity, digestion and gut health were analysed in the young rabbit, in response to fibre substitution by starch, in diets with high proportions of rapidly fermentable polysaccharides (pectins þ hemicelluloses:acid-detergent fibre (ADF) ratio of 1·7). A range of five diets corresponding to a 60 % linear reduction of the ADF level (230 to 92 g ADF/kg) without changes in the fibre quality, and to a corresponding linear increase in dietary starch, was given ad libitum to young rabbits from 18 d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 35 publications
5
41
0
5
Order By: Relevance
“…The DgF fraction plays a key role in digestive efficiency and digestive health, as it is rapidly fermented (compared with Mortality after weaning % Dietary ADF concentration, % as fed Gidenne et al, 2004bGidenne et al, 2004aDebray et al, 2002Bennegadi et al, 2001Perez et al, 1996Perez et al, 1994Perez et al, 1994Blas et al, 1994Carraro et al, 2007 Tazzoli 2012 CP15 Tazzoli 2012CP17 De Blas et al, 1981Maître et al, 1990 Figure 4 The rabbit post-weaning mortality decreases when the dietary lignocellulose (ADF) concentration increases, but with a highly variable impact within the classical dietary ADF range (15% to 22%). Data from 12 studies and 46 diets, without antibiotics, and varying in their ADF concentration.…”
Section: Brief Overview Of Polymers Of the Plant Cell Wall: Definitiomentioning
confidence: 99%
See 3 more Smart Citations
“…The DgF fraction plays a key role in digestive efficiency and digestive health, as it is rapidly fermented (compared with Mortality after weaning % Dietary ADF concentration, % as fed Gidenne et al, 2004bGidenne et al, 2004aDebray et al, 2002Bennegadi et al, 2001Perez et al, 1996Perez et al, 1994Perez et al, 1994Blas et al, 1994Carraro et al, 2007 Tazzoli 2012 CP15 Tazzoli 2012CP17 De Blas et al, 1981Maître et al, 1990 Figure 4 The rabbit post-weaning mortality decreases when the dietary lignocellulose (ADF) concentration increases, but with a highly variable impact within the classical dietary ADF range (15% to 22%). Data from 12 studies and 46 diets, without antibiotics, and varying in their ADF concentration.…”
Section: Brief Overview Of Polymers Of the Plant Cell Wall: Definitiomentioning
confidence: 99%
“…A similar relationship is obtained when we related the criteria 'TDF − ADF' to mortality. The favourable effect of DgF (compared with starch) on health would originate from a stimulated caecal fermentative activity (Garcia et al, 2002), and possibly from their moderate effect on the rate of passage (Gidenne et al, 2004a). This relationship between DgF and digestive health status is improved by using the HRi (more precise than mortality rate).…”
Section: Brief Overview Of Polymers Of the Plant Cell Wall: Definitiomentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, ileal flow of nutrients through the ileo-caecal junction will subsequently influence the caecal microbial activity, and it would be related to the incidence of digestive disorders in the young rabbit (Gidenne et al, 2004). Although, amylase and disaccharidases activities are low until 35 days of age (Corring et al, 1972;Dojanȃ et al, 1998), it has recently been shown that a high ileal flow of starch did not disturb either the caecal fermentation (Gidenne et al, 2005a) or the digestive health (Gidenne et al, 2005b) in growing rabbits.…”
Section: Introductionmentioning
confidence: 99%